The Effect of Organizational Culture, Job Satisfaction and Work Motivation on Teacher Performance Through Competence on Muhammadiyah High School Teachers in Purwokerto - Nuryanti Nuryanti; Erny Rachmawati; Sri Wahyuni; Hengky Widhiandono (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to ascertain how organizational culture, work motivation, and job satisfaction affect teachers' performance. The purpose of this research is to test hypotheses in explanatory research using a quantitative approach, and to explain the position and relationship between the variables being measured. Up to 112 respondents who were teachers made up the study's population. In this study, a sample of the entire population was used. Structural Equation Modeling (SEM) and Amos version 3.2 were used to analyze the data obtained from a questionnaire. Work motivation has a positive effect on teacher performance, Work motivation has a negative effect on competence, Competence has a negative effect on teacher performance, Organizational culture has a negative effect on teacher performance through competence, Job satisfaction has a negative effect on teacher performance through competence, and Work motivation has a negative effect on teacher performance through competence. These research findings demonstrate the influence of organizational culture on teacher performance, its positive effect on competence, and its negative effect on job satisfaction.